How Can Intelligent Educational Technologies Address the Challenges of Professional Retraining in Africa: From Current State to Future Perspectives? - (:unkn) unknown (My University, 2025)
Intelligent Educational Technologies (IET) have made it possible to change and transform education-related paradigms by offering a personalized and adaptive learning path. In Africa, where digital education is gaining momentum, IETs can play an important role in helping people retrain as web developers. This study explores the evolution and potential IET in the context of professional retraining in web development, with a specific focus on African working professionals. The article traces the history of IET, from early intelligent tutoring systems to current adaptive learning platforms, examining their architectures, models, and techniques. It analyses the effectiveness of these technologies in adult education and continuous learning, highlighting their advantages in terms of personalization and engagement. The study sheds light on the potential of IET for learning web development, particularly their accessibility and flexibility. However, it also addresses persistent challenges, such as adapting to the specific needs of learners in retraining process and developing transversal skills. The article raises critical considerations about the use of IET and concludes with future perspectives, highlighting the growing role of AI in democratizing continuing education, while calling for a balanced approach that integrates the principles of andragogy. Recommendations for enhancing IET adoption in Africa are also discussed.
Keywords: African Research